Next-Gen Cinema : Release and Marketing Strategies for Gen Z Engagement - Serper, Assel; Tahal, Radek, 1970-; Stříteský, Václav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The thesis explores how cinemas can better attract Generation Z audiences in the face of digital streaming competition and evolving consumer behavior. Focusing on the Czech market, it identifies key factors influencing Gen Z's cinema attendance, including their preferences for personalized marketing, innovative promotional approaches, and enhanced cinema experiences. Through theoretical and practical analysis, including a survey, this thesis paper proposes strategies that leverage digital tools, social media, and tailored experiences to increase engagement. The findings conclude the importance of aligning marketing and release initiatives with Gen Z's values, preferences, and consumption patterns. The thesis offers practical recommendations for cinemas to stay relevant by addressing the unique needs of this demographic group. It also adds theoretical value by contributing to literature on marketing, consumer behavior, and cinema engagement.
Vedoucí práce: Radek Tahal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses